Value of FDG PET/CT in Predicting Pathologic Complete Response After Neoadjuvant Chemotherapy in Locally Advanced Breast Cancer - KÖSTEK, OSMAN (My University, 2022)
Objectives: To investigate the importance of FDG PET/CT in predicting pathologic complete response (pCR) in primary breast lesions and axillary lymph nodes of patients with local, advanced breast cancer who were given neoadjuvant chemotherapy (NAC). Methods: One hundred twenty-one patients who had FDG PET/CT and underwent surgery due to local, advanced breast cancer before and after NAC were involved in the study. SUVmax and SULpeak values before and after NAC were evaluated using FDG PET/CT and post-surgical responses were re-evaluated. Results: Our study included 121 patients in total and 34 patients (28.1%) had a complete response in the breast, and 53 patients (43.8%) had a complete response in axillary lymph nodes. PostSUVmax and PostSULpeak values ≤1.15 and the activity presenting the pCR were controlled and the sensitivity and specificity were found as 61.8% and 61.8%, and 73.3% and 77.0%, respectively, for the breast (p<0.001 and p<0.001). The reduction rate (RR) of SUVmax >88% and the SULpeak (RR) >81% values and the activity presenting the pCR were controlled and the sensitivity and specificity were found as 80.0% and 81.8%, and 80.0% and 60.7%, respectively, for the breast (p<0.001 and p<0.001). Conclusion: The decrease of SUVmax and SULpeak values detected between PET/CT studies before and after NAC were well correlated with the pathologic response. FDG- PET/CT has high sensitivity and specificity in the evaluation of treatment response rates in breast lesions of patients with breast cancer receiving NAC
Keywords: Breast cancer; neoadjuvant chemotherapy; FDG Pet/CT; pathologic complete response